Kindergartens Teachers Early Detection Knowledge about Autism Spectrum Disorder in Babylon Province - Hadi, Mahdi Saleh (International Journal of Psychosocial Rehabilitation, 2020)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder that may cause difficulties with thought, feeling, language, social interaction and communication and the average age of diagnosis of ASD is about 4 to 5 year old. The aims of this study was to assess early detection knowledge of kindergartens teachers towards ASD and to compare between governmental and non-governmental kindergartens in relation to knowledge. A cross-sectional study design was used in Babylon province at kindergartens, on participants consist of (ɳ=204) teachers from two administrative departments that selected randomly by cluster sampling approach as 50% of total administrative departments. The result of this study indicate that the majority of kindergartens teachers having a moderate level of early detection knowledge, which constitute as (70.6%) and there is a significant difference between the governmental and private institution in relation to overall knowledge concerning early detection of ASD (knowledge of private kindergarten teachers higher than governmental). Therefore, the study recommends that: a great importance for educating and training the unusual educators in detecting and managing of children with ASD as a phase of children affected under growing universally, as well as development of continual educational training courses, seminars and workshop that held by the Ministry of Education for teachers focusing on the issue of ASD.